Low-enthalpy geothermal systems for air conditioning: a case study in the Mediterranean climate. (August 2018) - Frau, Caterina; Maggio, Enrico; Poggi, Francesca; Melis, Emanuela; Floris, Francesco; Orrù, Pier Francesco
Abstract: This paper presents a preliminary evaluation of the technical and economic feasibility of a low-enthalpy geothermal system for air conditioning and its integration with other systems, including a photovoltaic plant and an electrical storage system. The pilot building is a research center located in the southern side of the Mediterranean basin (Sardinia, Italy). Preliminarily, the main geological, hydrogeological and geothermal characteristics of the area were analyzed. Then, an energetic assessment of the building and its plants was performed. The hourly production of a photovoltaic plant already designed for the building was assessed. To improve the energy efficiency and the thermal energy self-consumption, an alternative thermal generation plant was proposed to replace the existing air conditioning system: a water-water heat pump coupled with a low-enthalpy geothermal probe (vertical configuration), to be embedded into the ground or placed into an existing groundwater well. The feasibility of electric storage was evaluated by considering a system capacity of 100 kWh to temporarily store and self-consume the electricity overproduced by the photovoltaic plant. A preliminary economic assessment showed the viability of the photovoltaic system. The 100 kWh-capacity electric storage will increase the self-production percentage, but it is not economically affordable. The replacement of the current air-water heat pumps with one water-water heat pump will be economically convenient if coupled with a groundwater geothermal probe, but the solution of a vertical probe embedded into the ground is unsustainable, due to high drilling costs.